Consumption and dietary intake of fruits and vegetables in Sri Lanka with a focus on traditional and indigenous fruits and vegetables - Silva, R; Sitisekera, H; Ranathunga, T; Perera, T; Hunter, D.; Borelli, T (2023)
Suboptimal diets are a significant preventable risk factor for non-communicable diseases (NCDs). Low- and middle-income countries (LMICs) often consume insufficient levels of fruits and vegetables (F&V), falling below recommended dietary intakes. To address this issue, detailed individual-level dietary data are needed to determine the extent and underlying factors contributing to inadequate F&V consumption. Additionally, understanding variations in F&V consumption across different life stages, genders, and demographic and socio-cultural factors is essential.